Influence of Quenching Agents on Mechanical, Wear, and Fracture Characteristics of Al2O3 / MoS2 Reinforced Al-6061 Hybrid Metal Matrix Composite (MMCs) - K. R. Suchendra; M. Sreenivasa Reddy; M. Ravikumar (Fracture and Structural Integrity)
Aluminium (Al) based composites enhance the mechanical and wear behavior by heat treatment. The quenching factors like cooling agent, cooling rate and temperature of cooling are expected to influence the hardness, tensile, and wear behavior of the Al MMCs. This research shows the outcomes of a sequence of experiments to find the wear and mechanical behavior of the Al6061-Al2O3-MoS2 hybrid composites are quenched with different quenching agents. Hardening of the developed hybrid composites was carried out at 510ºC for the time period of 2 hours. Later, the same composite samples were quenched in ice cubes and water separately. Finally, age-hardening was done at 180ºC temperature for 4 hours and then the samples were cooled under room temperature. Heat treated hybrid composites were subjected to evaluate the hardness, tensile, and wear behavior. The outcomes reveal that the heat treatment significantly enhances the wear and mechanical behavior of hybrid composites. High mechanical strength and improved wear characteristics were observed in the hybrid composites which were quenched using ice cubes. The fractured surface of the tensile test samples and the wornout surface of wear test specimens were studied using a SEM analysis.